1972
DOI: 10.2307/1218225
|View full text |Cite
|
Sign up to set email alerts
|

Chemistry of Lichen Substances

Abstract: JSTOR is a not-for-profit service that helps scholars, researchers, and students discover, use, and build upon a wide range of content in a trusted digital archive. We use information technology and tools to increase productivity and facilitate new forms of scholarship. For more information about JSTOR, please contact support@jstor.org. . International Association for Plant Taxonomy (IAPT) is collaborating with JSTOR to digitize, preserve and extend access to Taxon. This first bibliography of Irish lichenology… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
30
0
6

Year Published

1977
1977
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(38 citation statements)
references
References 0 publications
2
30
0
6
Order By: Relevance
“…The following studies confirm its generality and synthetic usefulness, as seen by the greatly improved preparation of the naturally occurring lichen substance (+)-isousnic acid (1) (4)(5)(6).…”
supporting
confidence: 60%
See 1 more Smart Citation
“…The following studies confirm its generality and synthetic usefulness, as seen by the greatly improved preparation of the naturally occurring lichen substance (+)-isousnic acid (1) (4)(5)(6).…”
supporting
confidence: 60%
“…The minor components obtained from the basic treatment of 3 result from both Michael addition of water (solvent) to the C,-C,, double bond and alkali cleavage of the nonenolizable C, carbonyl group producing the C,,-hydroxylated derivative 4 and the unsaturated acid 6 respectively (Fig. 1).…”
mentioning
confidence: 99%
“…In previous preliminary investigations (9) it was shown that various microorganisms have the ability to degrade the lichen antibiotic (+)-usnic acid (1) (10)(11)(12) and a more detailed study was now warranted. For this purpose a sample of Pseudomonas was obtained from surface soil samples collected in the Whistler mountain area of British Columbia and further experiments were undertaken.…”
mentioning
confidence: 99%
“…Chemical structures of secondary metabolites have been previously reported by Culberson (1969) and Asahina and Shibata (1971). …”
Section: Isolation Of Lichen Secondary Metabolitesmentioning
confidence: 96%